2013
DOI: 10.1186/1475-2859-12-102
|View full text |Cite
|
Sign up to set email alerts
|

A novel multigene expression construct for modification of glycerol metabolism in Yarrowia lipolytica

Abstract: BackgroundHigh supply of raw, residual glycerol from biodiesel production plants promote the search for novel biotechnological methods of its utilization. In this study we attempted modification of glycerol catabolism in a nonconventional yeast species Yarrowia lipolytica through genetic engineering approach.ResultsTo address this, we developed a novel genetic construct which allows transferring three heterologous genes, encoding glycerol dehydratase, its reactivator and a wide-spectrum alcohol oxidoreductase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
36
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(44 citation statements)
references
References 67 publications
7
36
0
1
Order By: Relevance
“…Later, the authors of the last article improved the process of CA production up to 52.0 g L −1 with the product yield (Y CA ) of 0.64 g g −1 using strain Y. lipolytica ACA-YC 5033, which was also able to remove harmful phenolic compounds from olive mill wastewaters [29]. The glycerol-grown yeast Y. lipolytica NRRL YB-423 produced 21.6 g L −1 of CA with mass yield of 0.54 g g −1 [12]; strain Y. lipolytica ACA-DC 50109 synthesized 62.5 g L −1 of CA with mass yield of 0.56 g g −1 from raw glycerol [20], while the recombinant strain Y. lipolytica NCYC3825 was able to produce 58 g L −1 of CA [30]. Earlier, we indicated that the other mutant Y. lipolytica NG40/UV7 synthesized, CA (122.2 g L −1 ) with the yield of 0.95 g g −1 .…”
Section: Resultsmentioning
confidence: 99%
“…Later, the authors of the last article improved the process of CA production up to 52.0 g L −1 with the product yield (Y CA ) of 0.64 g g −1 using strain Y. lipolytica ACA-YC 5033, which was also able to remove harmful phenolic compounds from olive mill wastewaters [29]. The glycerol-grown yeast Y. lipolytica NRRL YB-423 produced 21.6 g L −1 of CA with mass yield of 0.54 g g −1 [12]; strain Y. lipolytica ACA-DC 50109 synthesized 62.5 g L −1 of CA with mass yield of 0.56 g g −1 from raw glycerol [20], while the recombinant strain Y. lipolytica NCYC3825 was able to produce 58 g L −1 of CA [30]. Earlier, we indicated that the other mutant Y. lipolytica NG40/UV7 synthesized, CA (122.2 g L −1 ) with the yield of 0.95 g g −1 .…”
Section: Resultsmentioning
confidence: 99%
“…high biomass of 42 g/L and a peak lipid accumulation of 38% of total lipids in the dry cellular weight (DCW) were accumulated (Celińska and Grajek, 2013a).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…2-Phenylethanol, a rose-like aroma compound, has many potential applications.It can be naturally synthesized by different microorganisms. Recently, it was demonstrated that Y. lipolytica is deemed a novel 2-phenylethanol producer Celińska and Grajek (2013a). demonstrated that 2-phenylethanol is produced as a by-product together with citric acid production with glycerol as a carbon source.…”
mentioning
confidence: 99%
“…Recently, lipid accumulation has been found in the Y. lipolytica strains grown on glycerol in the range of 37.1-54.4% of cell dry weight (Sriwongchai et al, 2013). The introduction of heterologous glycerol dehydratase genes and several alcohol oxidoreductases under the control of glycerol inducible promoter, G3P dh, gave rise to a higher growth rate and a lipid yield at13 g/L of culture volume (40% of DCW) (Celinska and Grajek, 2013). This could be enhanced by the codon optimization of the heterologous genes and the prevention of further degradation of accumulated lipid.…”
Section: Strategies Associated With Extension Of Substrate Rangementioning
confidence: 99%